Surgical complications and their impact on patients’ psychosocial well-being: a systematic review and meta-analysis - Pinto, Anna (BMJ Open, 2016)
OBJECTIVE: Surgical complications may affect patients psychologically due to challenges such as prolonged recovery or long-lasting disability. Psychological distress could further delay patients’ recovery as stress delays wound healing and compromises immunity. This review investigates whether surgical complications adversely affect patients’ postoperative well-being and the duration of this impact. METHODS: The primary data sources were ‘PsychINFO’, ‘EMBASE’ and ‘MEDLINE’ through OvidSP (year 2000 to May 2012). The reference lists of eligible articles were also reviewed. Studies were eligible if they measured the association of complications after major surgery from 4 surgical specialties (ie, cardiac, thoracic, gastrointestinal and vascular) with adult patients’ postoperative psychosocial outcomes using validated tools or psychological assessment. 13 605 articles were identified. 2 researchers independently extracted information from the included articles on study aims, participants’ characteristics, study design, surgical procedures, surgical complications, psychosocial outcomes and findings. The studies were synthesised narratively (ie, using text). Supplementary meta-analyses of the impact of surgical complications on psychosocial outcomes were also conducted. RESULTS: 50 studies were included in the narrative synthesis. Two-thirds of the studies found that patients who suffered surgical complications had significantly worse postoperative psychosocial outcomes even after controlling for preoperative psychosocial outcomes, clinical and demographic factors. Half of the studies with significant findings reported significant adverse effects of complications on patient psychosocial outcomes at 12 months (or more) postsurgery. 3 supplementary meta-analyses were completed, 1 on anxiety (including 2 studies) and 2 on physical and mental quality of life (including 3 studies). The latter indicated statistically significantly lower physical and mental quality of life (p<0.001) for patients who suffered surgical complications. CONCLUSIONS: Surgical complications appear to be a significant and often long-term predictor of patient postoperative psychosocial outcomes. The results highlight the importance of attending to patients’ psychological needs in the aftermath of surgical complications.